Development of a Solar-Powered Submersible Pump System Without the Use of Batteries in Agriculture - Saurabh K. Bhosale (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to describe the development of a solar-powered submersible pump system without the use of batteries in agriculture. The submersible pump system used a solar drive to run it. The implementation uses a combination of solar trackers, water storage tanks, power converters, and stabilizers. The results of the study explained that solar trackers increased the efficiency of solar units that track the sun throughout the day and convert solar energy into DC electrical power.